3g, 4g and beyond : bringing networks, devices, and the web together - Sauter, Martin (Chichester, West Sussex, UK : John Wiley and Sons, 2013)
Extensively updated evaluation of current and future network technologies, applications and devices Written in a clear, concise style, this second edition of the successful Beyond 3G: Bringing Networks, Terminals And The Web Together; LTE, WiMAX, IMS, 4G Terminals and the Mobile Web 2.0 is fully updated and expanded to include new sections including VoLTE, the evolution to 4G, mobile internet access, LTE-Advanced, Wi-Fi security and backhaul for wireless networks 3G, 4G and Beyond: Bringing Networks, Devices and the Web Together, 2nd Edition.
2.3.3.2 Uplink Data Transmission2.3.3.3 Physical Parameters; 2.3.3.4 From Slots to Frames; 2.3.3.5 Reference Symbols, Signals, and Channels; 2.3.3.6 Downlink: Broadcast Channel; 2.3.3.7 Downlink: Paging Channel; 2.3.3.8 Downlink and Uplink: Dedicated Traffic and Control Channels and their Mapping to the Shared Channel; 2.3.3.9 Downlink: Physical Layer Control Channels; 2.3.3.10 Uplink: Physical Layer Control Channels; 2.3.3.11 Dynamic and Persistent Scheduling Grants; 2.3.3.12 MIMO Transmission; 2.3.3.13 LTE Throughput Calculations; 2.3.3.14 Radio Resource Control.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Wireless Internet; Wireless communication systems; Mobile communication systems; Smartphones; Mobile computing; Long-Term Evolution (Telecommunications); Wireless Internet; Wireless communication systems; Mobile communication systems; Smartphones; Mobile computing; Long-Term Evolution (Telecommunications); TECHNOLOGY & ENGINEERING -- Mobile & Wireless Communications; Long-Term Evolution (Telecommunications); Mobile communication systems; Mobile computing; Smartphones; Wireless communication systems; Wireless Internet; Wireless Internet; Wireless communication systems; Mobile communication systems; Smartphones; Mobile computing; Long-Term Evolution (Telecommunications); Electronic books; Electronic books